6 - Civil-Military Relations in the Transition to Democracy: The Case of Mozambique: 10.4314/ad.v24i3.22129 - Joao Bernardo Honwana (Africa Development, 1999)
In the last few years, Southern Africa has been forced to grapple with and redefine security priorities in a more complex post-war period. Issues like demilitarisation, resettlement, and restructuring of the armed forces in a way that contained erstwhile warring groups have become more strident than ever in the region. The paper focuses on the restructuring of the Mozambican armed services, which is taking place in the context of profound political transformations both at the domestic and regional levels. Its argument evolves around two main considerations: (i) that emerging democracies in Africa should espouse a concept of national security that adequately responds to the concerns of the citizens as much as those of the state, domestically, and promotes a common approach regionally; and (ii) that in this context, the armed services should be oriented in such a way that, they do not threaten the new democratic political order but to contribute positively to the consolidation of peace and national reconciliation.